Molecular characterisation of a case of dicentric Y presented as nonobstructive azoospermia with testicular early maturation arrest. (24th August 2017) - Kumar, P.; Jain, M.; Kalsi, A. K.; Halder, A.
Summary: The dicentric Y chromosome is the most common cytogenetically visible structural abnormality of Y chromosome. The sites of break and fusion of dicentric Y are variable, but break and fusion at Yq12 (proximal to the pseudoautosomal region 2/PAR 2) is very rare. Dicentric Y chromosome is unstable during cell division and likely to generate chromosomal mosaicism. Here, we report a case of infertile male with nonmosaic 46, XY where chromosome Y was dicentric with break and fusion at Yq12 (proximal to PAR 2). Clinical presentation of the case was nonobstructive azoospermia due to early maturation arrest at the primary spermatocyte stage. Various molecular techniques such as FISH, STS‐PCR and DNA microarray were carried out to characterise genetic defect leading to testicular maturation arrest in the patient. The break and fusion was found at Yq12 (proximal to PAR 2) and resulted in near total duplication of Y chromosome (excluding PAR 2). The reason for maturation arrest seems due to CNVs of PARs (gain in PAR 1 and loss of PAR 2) and azoospermia factors (gain).